Regulation of the immune microenvironment by SUMO in diabetes mellitus - Zhuo, Yuting; Fu, Shangui; Qiu, Yue (Frontiers in Immunology, 2025)
Post-translational modifications such as SUMOylation are crucial for the functionality and signal transduction of a diverse array of proteins. Analogous to ubiquitination, SUMOylation has garnered significant attention from researchers and has been implicated in the pathogenesis of various human diseases in recent years, such as cancer, neurological lesions, cardiovascular diseases, diabetes mellitus, and so on. The pathogenesis of diabetes, particularly type 1 and type 2 diabetes, has been closely associated with immune dysfunction, which constitutes the primary focus of this review. This review will elucidate the process of SUMOylation and its impact on diabetes mellitus development and associated complications, focusing on its regulatory effects on the immune microenvironment. This article summarizes various signaling pathways at both cellular and molecular levels that are implicated in these processes. Furthermore, it proposes potential new targets for drug development aimed at the prevention and treatment of diabetes mellitus based on insights gained from the SUMOylation process.